The Narrow and Broad Approaches to Evolutionary Modeling in Economics. Issue 2 (3rd April 2017) - Heinrich, Torsten
Abstract: Some models in evolutionary economics rely on direct analogies to genetic evolution, assuming a population of firms with routines, technologies, and strategies on which forces of diversity generation and selection act. This narrow conception can build upon previous findings from evolutionary biology. Broader concepts of evolution allow many or just one adaptive entity, instead of necessarily requiring a population. Thus, an institution or a society can also be understood as an evolutionary entity. Both the narrow and broad approaches have been extensively used in the literature, albeit in different literature traditions. I provide an overview of the conception and development of both approaches to evolutionary modeling, and argue that a generalization is needed to realize the full potential of evolutionary modeling.